Dose-dependent distribution of injected selenium in rat blood. Effect of previous selenium intake in drinking water - Stýblo, M; Kalousková, J; Pavlík, L (Journal of trace elements and electrolytes in health and disease, 1988)
The effect of an administered dose of 75Se-selenite and a previously increased selenium intake in drinking water (0.1 mg/l) on the distribution of injected selenium in rat blood was studied. In a dose range of 0.01-1.6 mg Se/kg body weight the ratio of injected selenium in blood plasma and in blood cells decreased from 3.20 in rats with increased selenium intake and 4.60 in rats without this intake, to 0.13 and 0.10, respectively. After injection of high selenite doses, 85-88% of the selenium present in the blood was localized in blood cells irrespective of increased selenium intake by drinking water. Possible relationship between accumulation of selenium in blood cells and its toxic effect in the organism is discussed. Previously increased intake of selenium had no effect on the levels of selenium in blood cells but affected significantly its plasma levels. The results indicate that the previously increased selenium intake in drinking water increases the capacity of the plasma for selenium injected in the form of selenite.
Keywords: injekce intraperitoneální; radioizotopy selenu; zvířata; Rats; pití; Time Factors; mužské pohlaví; Injections, Intraperitoneal; inbrední kmeny potkanů; Drinking; Selenium Radioisotopes; časové faktory; krysa rodu Rattus; Dose-Response Relationship, Drug; Rats, Inbred Strains; Animals; vztah mezi dávkou a účinkem léčiva; selen; Selenium; Male